Synchronous and metachronous multiple primary cancers in melanoma survivors: a gender perspective - Guzzinati, Stefano; Buja, Alessandra; Grotto, Giulia; Zorzi, Manuel; Manfredi, Mariagiovanna; Bovo, Eleonora; Del Fiore, Paolo; Tropea, Saveria; Dall’Olmo, Luigi; Rossi, Carlo R.; Mocellin, Simone; Rugge, Massimo (Frontiers in Public Health, 2023)
Background Long-term survivors of cutaneous malignant melanoma (CMM) risk subsequent malignancies due to both host-related and environmental risk factors. This retrospective population-based study differentially assesses the risk of synchronous and metachronous cancers in a cohort of CMM survivors stratified by sex. Methods The cohort study (1999–2018) included 9,726 CMM survivors (M = 4,873, F = 4,853) recorded by the cancer registry of all 5,000,000 residents in the Italian Veneto Region. By excluding subsequent CMM and non-CMM skin cancers, the incidence of synchronous and metachronous malignancies was calculated according to sex and tumor site, standardizing for age and calendar year. The Standardized Incidence Ratio (SIR) was calculated as the ratio between the number of subsequent cancers among CMM survivors and the expected number of malignancies among the regional population. Results Irrespective of the site, the SIR for synchronous cancers increased in both sexes (SIR = 1.90 in males and 1.73 in females). Both sexes also demonstrated an excess risk for synchronous kidney/urinary tract malignancies (SIR = 6.99 in males and 12.11 in females), and women had an increased risk of synchronous breast cancer (SIR = 1.69). CMM male survivors featured a higher risk of metachronous thyroid (SIR = 3.51, 95% CI [1.87, 6.01]), and prostate (SIR = 1.35, 95% CI [1.12, 1.61]) malignancies. Among females, metachronous cancers featured higher SIR values than expected: kidney/urinary tract (SIR = 2.27, 95% CI [1.29, 3.68]), non-Hodgkin’s lymphoma (SIR = 2.06, 95% CI [1.24, 3.21]), and breast (SIR = 1.46, 95% CI [1.22, 1.74]). Females had an overall increased risk of metachronous cancers in the first 5 years after CMM diagnosis (SIR = 1.54 at 6–11 months and 1.37 at 1–5 years). Conclusion Among CMM survivors, the risk of metachronous non-skin cancers is higher than in the general population and differs significantly by sex. These results encourage sex-tailored interventions for metachronous secondary cancer prevention.